Financing constraints, executive pay and gender inequality - Fernandes, Ana P. (2019)
This paper investigates the effect of financing constraints following the 2008-9 financial crisis on executive pay and gender inequality. We use linked employer-employee data for the universe of private sector firms in Portugal, and exploit pre-crisis variation in financial vulnerability across industries for identification. We find that the crisis had a negative effect on executive compensation and that firms in financially more constrained industries reduce the gender pay gap and increase the share of females in executive positions after the crisis. There is no evidence of an effect of the crisis on the pay-performance sensitivity. We also find that a higher share of female managers within firms is associated with higher sales and lower exit probability, both before and after the crisis. Our results suggest that the crisis induced firms in more financially constrained industries, who needed to perform better, to value more highly female managerial styles.